Context-dependent rewiring of dual-function proteins in cancer: a sequential strategy to restore apoptosis - Strzadala, Leon (Frontiers in Oncology, 2025)
Resistance to programmed cell death is a defining hallmark of cancer and a persistent barrier to successful therapy. Dual-function proteins such as p53, Ras, HIF-1α, BNIP3, and NF-κB act as molecular switches that determine cell fate between apoptosis and survival. In tumors, these proteins are deregulated not only by intrinsic mutations but also by extrinsic signals from the tumor microenvironment (TME). This Mini Review critically analyzes previous therapeutic approaches, emphasizing overlooked mechanisms such as Ras-mediated suppression of p53. It proposes a sequential therapeutic strategy: first, dismantling TME adaptations (hypoxia, inflammation, protective autophagy); second, inhibiting oncogenic Ras signaling; and third, restoring p53 activity. The phased approach integrates biomarker-guided patient stratification, recognizes tumor–microenvironment co-evolution, and highlights how resistance evolves over time. Although the concept does not resolve all challenges, it outlines a rational framework for restoring apoptotic competence and provides a pathway for translational and clinical testing.